Diagnostic Evaluation in Pediatric Abdominopelvic Trauma - Mir, Dr. Mohd. Altaf; Kumar, Prince (Pediatric Abdominopelvic Trauma, 2024)
This chapter provides a comprehensive exploration of the diagnostic evaluation process for pediatric abdominopelvic trauma, encompassing a holistic approach from history-taking to advanced imaging modalities and invasive procedures. Beginning with the crucial foundation of obtaining a detailed medical history, the chapter emphasizes the significance of a systematic physical examination, including primary survey, vital signs monitoring, and thorough systemic and local assessments. Special attention is dedicated to pediatric trauma scoring, offering a standardized framework for severity assessment. Moving into the investigative realm, the chapter meticulously outlines various laboratory investigations essential for unraveling the complexities of pediatric abdominopelvic trauma. The radiological evaluation is discussed in detail, encompassing traditional plain radiographs, the utility of Focused Assessment with Sonography for Trauma (FAST), and the emerging role of Contrast Enhanced Ultrasonography (CEUS). Additionally, the chapter delves into the pivotal role of Computed Tomography (CT) in providing detailed anatomical insights. In the realm of invasive procedures, the chapter navigates through the nuances of Diagnostic Paracentesis, Diagnostic Peritoneal Lavage, and laparoscopy. Each procedure is elucidated, shedding light on its indications, procedural aspects, and diagnostic contributions. This chapter serves as a comprehensive guide, equipping clinicians with a robust framework for navigating the intricate landscape of pediatric abdominopelvic trauma. By amalgamating clinical acumen with state-of-the-art diagnostic modalities, the chapter seeks to enhance the precision and effectiveness of diagnostic approaches, ultimately contributing to optimized medical management and improved outcomes in pediatric patients with abdominopelvic trauma.